Peran dan Fungsi Komunikasi Interpersonal Kepala Sekolah di SMP IT Ad Durrah - Sani, Dinda Aulia; Munawwarah, Tarisa; Kholizah, Nur Alfiana; Hanifah, Fathia; Savitri, Intan; Aswaruddin, Aswaruddin (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to understand the role and function of interpersonal communication in various contexts, both organizations and everyday life, using descriptive qualitative research methods. Data was collected through in-depth interviews and direct observation to explore participants' perspectives regarding the importance of interpersonal communication. The research results show that interpersonal communication plays a significant role in building relationships between individuals, increasing collaboration, resolving conflicts, and providing motivation and constructive feedback. In organizational life, interpersonal communication functions to create a harmonious work environment and increase team productivity. Meanwhile, in a personal context, this communication strengthens relationships, builds trust, and reduces misunderstandings. These findings confirm that interpersonal communication is a strategic element for creating meaningful connections in various aspects of life, including in the digital era.